International Student Recruitment: Trends and Challenges - Falcone, Santa (Journal of International Students, 2017)
This paper provides a review of current trends in international student recruitment. Focusing specifically on recruitment of Chinese students, important aspects of China’s educational system relevant to recruitment are presented. Barriers to Chinese student recruitment are then discussed. Successful, employed, international graduates validate domestic institutional value to prospective foreign students and their parents. In that regard, guidance is then offered for domestic universities to use to assist international students to achieve their desired outcomes as an integral part of the institution’s international student recruitment strategy.